Saving the Sustainability of the European Union, Fighting Terrorism - D, El Chami; M, El Moujabber (European Scientific Journal, ESJ, 2018)
Albeit the absence of an agreement on the definition, terrorism as studied in this literature has a complex nature and diverse factors that are involved. Furthermore, dealing with terrorism has become the centrepiece of foreign policies of many countries worldwide. The European Union has a long history of fighting terrorism. Yet, the current terrorism threats have shaken the bases of the Union. According to the authors’ assessment and evaluation, terrorism in Europe, in the aftermath of the Second World War, occurs due to the unsustainable foreign policies of the EU member states. To save the European Union and to fight terrorism, the authors suggest a framework based on four complementary headlines: i) Education, ii) Social justice and human rights, iii) Law enforcement, and iv) Sustainable common defence policy. A prerequisite to the success of this framework is a revision of the Europe-transatlantic relations to address the imbalance in the EU relations with USA.